Punxsutawney Phyllis - Hill, Susanna Leonard (Holiday House, 2005)
Although she can predict the weather much better than the boys in her family, no one thinks that Phyllis the groundhog has a chance of replacing the aging Punxsutawney Phil when Groundhog Day's official groundhog retires.